Power system dynamics : stability and control - Machowski, Jan; Lubosny, Zbigniew, 1961-; Bialek, Janusz W.; Bumby, J. R. (James Richard) (Hoboken, NJ, USA : John Wiley, 2020)
"This book is the fully revised and updated third edition of Power System Dynamics and Stability. It has been 10 years since the second edition was published and the state of the knowledge in the topic area has progressed. The textbook requires updating and extending. A third edition will include an extension of some chapters and four new chapters"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Electric power system stability; Electric power systems -- Control